Facile synthesis of ROS-responsive biodegradable main chain poly(carbonate-thioether) copolymers. Issue 7 (31st January 2018) - Yan, Bingkun; Zhang, Yan; Wei, Chao; Xu, Yue
Abstract : The amphiphilic main chain poly(carbonate-thioether) copolymers were synthesized based on a novel macrocyclic sulfur-substituted carbonate monomer. The assembled nanostructures have rich ROS responsiveness. Abstract : Oxidation-responsive thioether-functional polymers have emerged as potential materials for biomedical applications. Herein, we report the straightforward synthesis of a well-defined biodegradable thioether-containing polycarbonate (mPEG- b -PS) based on the macrocyclic sulfur-substituted carbonate monomer (MS) using an enzyme-catalyzed ring-opening polymerization with the thioether groups situated on the backbone. NMR, FTIR and GPC techniques were employed to confirm the structure of the copolymers. Moreover, the thioether groups endowed the copolymers with rich ROS responsiveness and the oxidation mechanism was clarified according to in situ 1 H-NMR, FTIR and TGA data. In addition, the water contact angles testified that the hydrophilicity of the copolymers was greatly improved during the H2 O2 triggered oxidation process. The thioether oxidation to polar sulfone and sulfoxide groups enabled us to tailor the copolymer's solubility profile; thus, the size, morphology and transmittance of the nanostructure changed according to the results obtained using DLS, TEM and UV techniques. Furthermore, CCK-8 assays showed that the thioether-containing polycarbonate and their oxidized products were non-toxic up to a tested concentration of 250 μg mL −1 . Moreover, the mPEG- b -PS had a definite H2 O2 -triggered drug release behaviour. Therefore, these results highlight a facile synthesis of biodegradable thioether-containing polymers and provide a novel ROS responsive material platform for further cancer therapy and inflammation targeting.